2018
DOI: 10.1507/endocrj.ej18-0290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the modification of the diagnostic criteria in the 2017 Bethesda System for Reporting Thyroid Cytopathology: a report of a single institution in Japan

Abstract: The Bethesda System for Reporting Thyroid Cytopathology has recently been revised in 2017 (TBSRTC 2017). This study aimed to evaluate the impact of modifying the diagnostic criteria in TBSRTC 2017 at a single institute. We retrospectively reviewed cytological specimens of 10,399 thyroid nodules submitted for thyroid fine-needle aspiration cytology. Among them, 56 atypia of undetermined significance or follicular lesion of undetermined significance (AUS/FLUS) nodules, 16 suspicious for malignancy (SFM) nodules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Clinicians are also able to prevent overtreatment by considering not only cytological diagnosis but also ultrasound findings. Higuchi M, et al [27] reported that active surveillance (follow-up without surgical resection) is an acceptable option for thyroid nodules having favorable benign clinical findings or benign part of the lowrisk group.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians are also able to prevent overtreatment by considering not only cytological diagnosis but also ultrasound findings. Higuchi M, et al [27] reported that active surveillance (follow-up without surgical resection) is an acceptable option for thyroid nodules having favorable benign clinical findings or benign part of the lowrisk group.…”
Section: Discussionmentioning
confidence: 99%
“…TBSRTC recommends that in cases where morphology raises the possibility of NIFTP (microfollicular architecture, lack of papillary structures, partial PTC nuclear features) an educational note should be added. It is yet to be determined whether ancillary studies would be able to distinguish between NIFTP and other morphologically similar tumours that exhibit more aggressive behaviour 7,40 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the diagnosis of non-invasive type EFV-PTC has been reframed as NIFTP [7]. However, it is difficult to morphologically distinguish the presence or absence of invasion, pre-operatively, besides the observer-associated variations in the identification of nuclear features of PTC [8,33,34]. Identification of a suitable marker that can distinguish between the presence and absence of invasion would significantly contribute to the reduction of excision region as well as in precise treatment.…”
Section: Discussionmentioning
confidence: 99%